Analisis Faktor Ekonomi Makro Penerimaan Negara Bukan Pajak (Studi Kasus Kota Batang) - Utami, Novi Dhian; Syaifudin, Noor; Patiro, Shine Pintor Siolemba (Jurnal Rumpun Ilmu Ekonomi, 2024)
This research analyzes the influence of macroeconomic factors on Non-Tax State Revenue (PNBP) in Batang City in the 2020-2023 period. Using monthly data from Bank Indonesia and the Central Statistics Agency, this research applies the Vector Autoregression-Vector Error Correction Model (VAR-VECM) method to see the short-term and long-term relationship between PNBP and variables such as Gross Regional Domestic Product (GRDP), inflation, exchange rates, and interest rates. The research results show that macroeconomic factors significantly influence PNBP in the long term, although the influence is not visible in the short term. Policymakers need to pay attention to a combination of external and internal factors, such as fiscal and monetary policies, to optimize state revenues from non-tax sources in the future. This research also emphasizes the importance of sustainable policy planning to anticipate the long-term impact of global economic fluctuations on PNBP.